2021
DOI: 10.1371/journal.pone.0250195
|View full text |Cite|
|
Sign up to set email alerts
|

High burden of cryptococcal antigenemia and meningitis among patients presenting at an emergency department in Maputo, Mozambique

Abstract: Background Cryptococcal meningitis is a leading cause of HIV-related mortality in sub-Saharan Africa, however, screening for cryptococcal antigenemia has not been universally implemented. As a result, data concerning cryptococcal meningitis and antigenemia are sparse, and in Mozambique, the prevalence of both are unknown. Methods We performed a retrospective analysis of routinely collected data from a point-of-care cryptococcal antigen screening program at a public hospital in Maputo, Mozambique. HIV-positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
3
10
1
Order By: Relevance
“…Results of this study show that Cryptococcus neoformans is responsible for 38.6% of all laboratory-confirmed cases, thus making it the leading cause of meningitis among adults. These are similar to previously reported findings from other Sub-Saharan African countries, having found frequencies ranging from 60.5% to 71.6% [ 1 , 11 , 16 , 33 38 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Results of this study show that Cryptococcus neoformans is responsible for 38.6% of all laboratory-confirmed cases, thus making it the leading cause of meningitis among adults. These are similar to previously reported findings from other Sub-Saharan African countries, having found frequencies ranging from 60.5% to 71.6% [ 1 , 11 , 16 , 33 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…We also investigated predictors for meningitis in adults in Mozambique and found that CD4 cell count < 100 cells/μL had strong association (aOR = 59, p = 0.001) with meningitis, as also reported in other countries [ 1 , 11 , 13 , 49 51 , 54 61 ].…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations